D’anaesthésie Et D’analgésie Loco-Régionale: Coup D’oeil through the past, the present and the future. - Mohamed Zaini, Mohamed Asri; Borhan, Muhammad Salman; Ibrahim, Mohd Fauzi; Abd Ghani, Muhamad Rasydan (Malaysian Society of Anaesthesiologists, 2021)
Since K. Koller introduced the first regional anaesthesia with cocaine in 1846, it has evolved rapidly. Regional anaesthesia has become the contemporary anaesthesia approach to facilitate surgical procedures and promote patient safety, thanks to break throughs in pharmacology, knowledge in medicine and innovative technology. In recent years, regional anaesthesia techniques have been used as part of multimodal analgesia for patients rather than as the primary anaesthetic strategy during surgery. It is used in conjunction with general anaesthesia, which effectively reduces the use of systemic analgesics such as morphine and non-steroidal anti-inflammatory agents. This article revisits its past, highlights current practices and its potential future as it evolves.